Determinant Factors of Unmet Need in Family Plannung (FP): A Systematic Review - Ifayanti, Titin (citeus, 2024)
Unmet Needs in family planning (FP) remain a concern in many countries worldwide and can, therefore, adversely affect women, families, and society. Around 12 percent of women worldwide have an unmet need. Such effects include widespread disease, increased maternal mortality, and psychological disorders among women. This study aimed to elucidate the factors associated with the unmet need for family planning. The research approach used was a systematic review, literature was identified through Google Scholar, PubMed, and (NLM): National Library of Medicine. A systematic review and literature analysis of 9 articles was carried out, which utilized secondary data and cross-sectional study designs. Unmet needs are significantly related to maternal age as well as educational level. Unmet needs are generally higher among younger and less educated women than among those with higher levels of education. Therefore, it is recommended to provide appropriate health education related to contraception and family planning to women and their families to enable better decision-making regarding their reproductive health. Furthermore, improved access to contraception can reduce the prevalence of unmet needs in family planning.